2002
DOI: 10.1108/13612020210448673
|View full text |Cite
|
Sign up to set email alerts
|

Differences in purchase behavior between France and the USA: the cosmetic industry

Abstract: This study investigates the differences in purchasing behavior between the US and French cosmetic markets. Our study suggests that a difference should exist due to psychological factors, social influences, and the purchase situation. Our paper will discuss the underlying theoretical perspectives that support our proposition, and illustrate the various components which influence consumer behavior in this particular marketplace. The analysis and investigation is based on the cosmetic industry in terms of compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…Social influence affects the ways other people affect one's beliefs, feelings and behavior (Manson et al, 2007). Social influence in this research is conceptualized to be the way other people or the environment will affect one's belief or behavior (Weber & Villebonne, 2002). This definition is in line with Ting et al (2011).…”
Section: Social Influencementioning
confidence: 88%
See 2 more Smart Citations
“…Social influence affects the ways other people affect one's beliefs, feelings and behavior (Manson et al, 2007). Social influence in this research is conceptualized to be the way other people or the environment will affect one's belief or behavior (Weber & Villebonne, 2002). This definition is in line with Ting et al (2011).…”
Section: Social Influencementioning
confidence: 88%
“…26;2015 207 The results of this study also showed that the hypothesis H 3 -social influence has a positive relationship with dependency on smartphone usages -was significant. As stated earlier, social influence was defined by Weber and Villebonne (2002) as a cultural environment that can influence one's behavior as well as influence the reasons why and how people live. Lu and Wang (2008) further expanded the concept of social influence to include its impact on the user's perception and behavior through two distinct constructs, i.e.…”
Section: Antecedents Of Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous earlier studies of crossnational differences in consumer behaviour in different consumption sectors have verified that cultural differences have a strong influence on consumers, to the extent that the same product or service may be perceived differently according to the culture of origin and determine individual behaviour (Mok & Amstrong, 1998;Mattila, 1999;Weber & Villebonne, 2002;Cunningham, Young, Lee, & Ulaga, 2006;Jin, Park, & Kim, 2008;Suiden & Diagne, 2009). Though it is true that the members of national communities have a wide diversity of individual cultural identities, it is also true that, over and above the individual cultural identity, there exists the national cultural identity (Tipton, 2009), although globalization and the internationalisation of markets has brought with it a process of transfer and construction of the meaning that implies new processes of identity formation, cultural hybridisation and "glocalization" (Gould and Grein, 2009).…”
Section: Cross-nationalmentioning
confidence: 99%
“…Such perspectives have been proven to have a considerable amount of impact on consumer behavior in cosmetics. Furthermore, in comparison to different countries of different background, previous research concluded that psychological and socio-cultural factors were the dominant reasons for a change in consumer behavior in the cosmetics industry in recent decades (Weber, 2002;Kumar, 2014;Morphitou, 2011). Not only did they focus on makeup products but also the remaining products in the cosmetics industry.…”
mentioning
confidence: 99%